المرجعية الدينية الشيعية والفضاء السياسي الاجتماعي: قراءة في تجربتي المرجعين محمد الصدر وعلي السيستاني - حسن، حارث (المركز العربي للأبحاث ودراسة السياسات, 2020)
Most studies dealing with the activities of Shi’i religious actors tend to classify them as falling within the binaries of politicized and non–politicized, or reformists and traditionalists. Often these binaries have ignored the importance of the different forms of religious activism and practices. This study is concerned with the importance of religious activism and its relationship to socio–political variables in shaping the movement of religious actors, focusing on the examples of Muhammad al–Sadr and Ali al–Sistani, who competed over the Marja’iyya at similar times. The paper argues that while Sadr developed his version of religious activism by blending the social and religious movement with the Islamization project, Sistani tended to separate between political and religious practice, and his presence in the public sphere was not framed with a specific ideological template.
تميل معظم الدراسات التي تتناول نشاط الفاعلين الدينيين الشيعة إلى تصنيفهم إلى مسيسين وغير مسيسين، أو إصلاحيين وتقليديين، وغالبا ما أدت هذه الثنائية إلى تجاهل الأشكال المختلفة من هذا النشاط والطيف الواسع الذي يجسده، والذي قد تندرج فيه غالبية هؤلاء الفاعلين. تحاول هذه الدراسة أن تعيد الاعتبار إلى أهمية ممارسة النشاط الديني وعلاقته بالمتغيرات الاجتما-سياسية في تشكيل حركة الفاعلين الدينيين، مركزة على نموذجي محمد الصدر وعلي السيستاني، اللذين تصديا للمرجعية في وقت متقارب زمنيا. وتجادل الدراسة بأنه في حين طور الصدر ممارسته عبر المزج بين الديني والحركية الاجتماعية المتلونة بمشروع الأسلمة المجتمعية، فإن السيستاني اتجه إلى الفصل بين الممارسة السياسية والممارسة الدينية، ولم يؤطر حضوره في المجال العام بقالب أيديولوجي محدد.
Keywords: المعتقدات الدينية -- المرجعية الدينية الشيعية -- الصدر ، محمد -- السيستاني ، علي -- الممارسة السياسية